Peningkatan Tata Kelola Keuangan SMAM 3 Pandaan Melalui Implementasi Good School Governance - Hariyono, Anwar; Handoko Putro, Guruh Marhaenis; Megasyara, Ira (JURNAL PENGABDIAN MANAJEMEN, 2025)
ABSTRACT This community service activity aims to enhance the quality of financial management at SMA Muhammadiyah 3 Pandaan by implementing the principles of Good School Governance (GSG). The Audit Team from the Financial Development and Supervision Agency (LPPK) of the Muhammadiyah Regional Leadership (PWM) of East Java conducted a compliance audit based on the school financial management regulations established by PWM East Java. The audit methods included data and document collection, field observations, data comparison and analysis, interviews with relevant parties, and confirmation of audit findings. The audit results highlighted the need for improvement in internal controls, compliance with government payments, and financial statement preparation according to accounting standards. The audit team provided improvement recommendations, including enhancing the internal control system, fulfilling government-mandated payments, and preparing financial statements in accordance with accounting standards. Implementing these recommendations will enhance financial management at SMA Muhammadiyah 3 Pandaan, ensuring compliance with regulations and promoting transparency and accountability in educational fund management.